Magnetic, magnetocaloric and structural properties of manganese based monoborides doped with iron and cobalt – A candidate for thermomagnetic generators. (July 2016) - Fries, Maximilian; Gercsi, Zsolt; Ener, Semih; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract: Refractory borides are good candidates for thermomagnetic energy conversion due to their high chemical stability and good magnetic properties. A systematic study focusing on the crystallographic, magnetic and magnetocaloric properties of cobalt and iron substituted MnB was conducted. The pure MnB sample shows an orthorhombic structure with a spontaneous magnetization ( M s ) of 156 Am 2 kg −1 and a sharp magnetic transition ( T C ) of 567 K that yields a large magnetic entropy change of 7.5 J kg −1 K −1 in a 2T field change at this temperature. Both the substitution of Co and Fe elements for Mn were found to effectively modify T C accompanied by a lower magnetization ( M s ) leading to a reduced magnetocaloric effect (MCE). The differences in magnetic properties with substitution are described by calculation of the density of states and interatomic distances. It is found that in contrast to the Co atoms the Fe atoms develop large and stable moments similar to the Mn atoms which is consistent with the experimental findings. The sharp and significant change of M s (T), the very stable nature of these refractory borides and abundant availability makes some of these compositions suitable for thermomagnetic power generation applications. Graphical abstract: